Harry Potter and the Half-Blood Prince - Rowling, J. K. (Scholastic Inc., 2018)
As they travel through their sixth year at Hogwarts, Harry and his friends receive help from the mysterious Half-Blood Prince in their search for the complete story of how Tom Riddle became Lord Voldemort and find in the process what might be Voldemort's only vulnerability.